Kebutuhan Media Gimkit pada Materi Mukjizat Kelas VIII MTs Darul Amin Palangka Raya - Badriah, Siti; Levia, Trisna (Pendidikan Agama Islam STIT Palapa Nusantara, 2025)
This study aims to analyze the need for the use of interactive media Gimkit in learning the material of miracles among students of class VIII MTs Darul Amin Palangka Raya. Conventional learning media is considered less effective, so technological innovation is needed. This study used a mixed method research with qualitative and quantitative approaches. Data were obtained through questionnaire results from 25 students, interviews with teachers, and observations during learning using Gimkit. The analysis results show that: 1) 60% of students really like game or quiz-based learning, 36% like it, and 4% feel normal; 2). 12% of students very often feel bored in learning, 36% are often bored, while 44% of students sometimes feel bored and 8% of students rarely experience boredom; 3). 48% of students feel very interested in the moral creed material delivered through games or quizzes, 44% feel interested, 4% are quite interested, and 4% feel less interested; 4). 44% of students felt very helped in understanding the material with Gimkit, 44% felt helped, and 12% felt quite helped. Thus, most students found it easier to understand the concept of miracles with Gimkit than the conventional method. This shows that Gimkit is effective as an interactive media in Islamic Religious Education and can be optimally integrated in learning. Gimkit is recommended as an innovative alternative to improve students' understanding of the concept of miracles.